Hidden behind the model minority stereotype: Exploring disparities and the role of parent empowerment in Asian students' college enrollment. Issue 4 (18th July 2022) - Kim, Jungnam; Bryan, Julia Green; Griffin, Dana; Sharma, Gitima
Abstract: We investigated the relationship between Asian parent empowerment and their children's college enrollment in a sample of 357 Asian parents from various ethnic subgroups using the High School Longitudinal Study 2009. A multinomial logistic regression indicated differences in Asian students' college enrollment by ethnic subgroup and income and in the role of personal and community parent empowerment in college enrollment. The results indicate the danger of the model minority myth in masking disparities among Asian students. Resumen: Investigamos la relación entre el empoderamiento de padres asiáticos y la matriculación universitaria de sus hijos en una muestra de 357 padres asiáticos de diferentes subgrupos étnicos usando los datos del High School Longitudinal Study 2009. Una regresión logística multinomial indicó diferencias en la matriculación universitaria de los estudiantes asiáticos por subgrupos étnicos e ingresos, así como en el papel del empoderamiento personal y comunitario de los padres sobre la matriculación universitaria. Los resultados indican el peligro causado por el mito de la minoría modelo al enmascarar las diferencias entre estudiantes asiáticos.